Blessing unintended pregnancy: Religion and the discourse of women’s agency in public health (Medicine Anthropology Theory, 2020)
Within public health and medical anthropology research, the study of women’s agency in reproductive decision making often neglects the role of religion and women’s spirituality. This article is based on ethnographic research conducted at a shelter for homeless (mostly African American) mothers in the southeastern United States. We explore the inadequacy of rational choice models that emphasize intentionality and planning, which our research shows are in tension with the vernacular religious and moral ethos of pregnancy as a ‘blessing’ or unplanned gift. Our findings confirm that young and disadvantaged women may view pregnancy and motherhood as opportunities to improve their lives in ways that mediate against their acceptance of family planning models. For these women, the notion of ‘blessing’ also reflects an acceptance of contingency and indeterminacy as central to the reproductive experience. We also question the increasingly popular distinction between ‘religion’ and ‘spirituality’ in contemporary public health.